Emergence of the Modern Academic Study of Religion: An Analytical Survey of Various Interpretations - Akram, Muhammad (Islamic Studies, 2016)
This paper discusses various interpretations about emergence of the academic study of religion in the modern world. It is viewed that the expansion of Europe and resultant engagement of European consciousness with religious and cultural otherness played a role. Internally, the Enlightenment movement had prepared ground for a critical and objectified gaze at the phenomenon of religion on the one hand while Romanticism had generated a kind of fascination for oriental religions and exotic cultures, on the other. Similarly, the Christian theology, which had already gone through transformation, is also linked to the whole enterprise either as a disciplinary other or as a participating actor. The paper shows that available interpretations of the development range from viewing it as an encroachment of the scientific project into the realm of religion to a marriage of convenience between science and religion. In the final analysis, an integrative and inclusive view of various interpretive narratives has been adopted. It is maintained that since the modern academic study of religion itself is characterised by diversity of approaches, theoretical perspectives, and regional contexts, therefore, heterogeneity of the narratives regarding its beginnings is but a logical consequence. Still, interrogation into these narratives is useful for better contextual understanding of various epistemological and methodological inclinations prevalent in the academic study of religion in our own times.